Practical genotyping by single-nucleotide primer extension - Breyer, Joan P (Biol Methods Protoc, 2020)
Genome-wide association studies bring into focus specific genetic variants of particular interest for which validation is often sought in large numbers of study subjects. Practical alternative methods are limiting for the application of genotyping few variants in many samples. A common scenario is the need to genotype a study population at a specific high-value single nucleotide polymorphism (SNP) or insertion-deletion (indel). Not all such variants, however, will be amenable to assay by a given approach. We have adapted a single-nucleotide primer extension (SNuPE) method that may be tailored to genotype a required variant, and implemented it as a useful general laboratory protocol. We demonstrate reliable application for production-scale genotyping, successfully converting 87% of SNPs and indels for assay with an estimated error rate of 0.003. Our implementation of the SNuPE genotyping assay is a viable addition to existing alternative methods; it is readily customizable, scalable, and uses standard reagents and a laboratory plate reader.